Low-sodium DASH diet improves diastolic function and ventricular-arterial coupling in hypertensive heart failure with preserved ejection fraction - Hummel, Scott L; Seymour, E Mitchell; Brook, Robert D; Sheth, Samar S; Ghosh, Erina; Zhu, Simeng; Weder, Alan B; Kovács, Sándor J; Kolias, Theodore J (Circulation. Heart failure, 2013)
Heart failure with preserved ejection fraction (HFPEF) involves failure of cardiovascular reserve in multiple domains. In HFPEF animal models, dietary sodium restriction improves ventricular and vascular stiffness and function. We hypothesized that the sodium-restricted dietary approaches to stop hypertension diet (DASH/SRD) would improve left ventricular diastolic function, arterial elastance, and ventricular-arterial coupling in hypertensive HFPEF. Thirteen patients with treated hypertension and compensated HFPEF consumed the DASH/SRD (target sodium, 50 mmol/2100 kcal) for 21 days. We measured baseline and post-DASH/SRD brachial and central blood pressure (via radial arterial tonometry) and cardiovascular function with echocardiographic measures (all previously invasively validated). Diastolic function was quantified via the parametrized diastolic filling formalism that yields relaxation/viscoelastic (c) and passive/stiffness (k) constants through the analysis of Doppler mitral inflow velocity (E-wave) contours. Effective arterial elastance (Ea) end-systolic elastance (Ees) and ventricular-arterial coupling (defined as the ratio Ees:Ea) were determined using previously published techniques. Wilcoxon matched-pairs signed-rank tests were used for pre-post comparisons. The DASH/SRD reduced clinic and 24-hour brachial systolic pressure (155 ± 35 to 138 ± 30 and 130 ± 16 to 123 ± 18 mm Hg; both P=0.02), and central end-systolic pressure trended lower (116 ± 18 to 111 ± 16 mm Hg; P=0.12). In conjunction, diastolic function improved (c=24.3 ± 5.3 to 22.7 ± 8.1 g/s; P=0.03; k=252 ± 115 to 170 ± 37 g/s(2); P=0.03), Ea decreased (2.0 ± 0.4 to 1.7 ± 0.4 mm Hg/mL; P=0.007), and ventricular-arterial coupling improved (Ees:Ea=1.5 ± 0.3 to 1.7 ± 0.4; P=0.04). In patients with hypertensive HFPEF, the sodium-restricted DASH diet was associated with favorable changes in ventricular diastolic function, arterial elastance, and ventricular-arterial coupling. URL: http://www.clinicaltrials.gov. Unique identifier: NCT00939640.